PEMANFAATAN AMPAS SAGU SEBAGAI BAHAN DASAR KOMPOS PADA BEBERAPA DOSIS PENCAMPURAN DENGAN KOTORAN SAPI - Wahida Wahida; Amelia Agustina Limbongan (Universitas Musamus, Merauke, Papua, 2015)
This research is about exploring the amount of sago waste as the basic ingredient of compost. The research aimed to change sago waste into useful organic compound in composting process. Ingredients used in this research were sago waste, cow dung, bran, palm sugar, water and Biosmik as the decomposer. The comparisons between sago waste and cow dung were 1 : 1, 2 : 1, and 3 : 1. The Biosmik used was 1 kg/ton compost material. This research was held at the Green House of Agriculture Faculty Musamus University Merauke. The research procedure included sago waste location survey, interviewing the local community about sago waste, taking the sago waste as the ingredient for compost, preparing ingredients and materials, making compost, and analyzing compost NPK sample. The result showed that treatment by which the sago waste and cow dung comparison = 2 : 1 is the best comparison that can be used as recommendation as a compost.